Sudden stops in the Euro Area: Does monetary union matter?. (November 2020) - Fagan, Gabriel; McNelis, Paul D.
Highlights: This paper compares adjustment in a fixed-exchange rate system under two regimes. In the monetary union, external funding is available to an economy through the common central bank. We model the external funding process based on an empirical analysis of the TARGET system in the Euro zone. We use a modified and re-calibrated version of the Mendoza model of sudden stops. Thesystem significantly mitigates the fall in GDP, consumption and investment. However a welfare comparison shows only modest welfare differences between the two regimes. Abstract: This paper examines how membership of a monetary union affects macroeconomic adjustment of Euro Area countries to sudden stops. We focus on a key feature of the monetary union: the availability of external financing from the common central bank reflected in TARGET balances. For this purpose, we use a modified version of the Mendoza (2010) model which incorporates central bank financing, based on an empirical analysis of TARGET flows. Our results show that the availability of such financing greatly mitigates the collapse in GDP, consumption and investment during sudden stops (relative to a regime in which such financing is not available). However, a welfare analysis shows that common central bank financing only results in modest welfare gains in the affected country, since it exacerbates the tendency towards over-borrowing, leading to an increased incidence of sudden stop episodes.